Prevalence of left ventricular systolic dysfunction in a typical outpatient pacemaker cohort - Schwerg, Marius (Herzschrittmacherther Elektrophysiol, 2020)
BACKGROUND: Right ventricular (RV) pacing is the standard treatment for symptomatic bradycardia. RV pacing is known to cause dyssyncrony. New treatment options like His bundle pacing enhance the focus on left ventricular dysfunction in patients with pacemakers. OBJECTIVES: The aim of this cross-sectional study was to obtain a real-life picture of the patients in a representative cohort of outpatients with permanent pacemakers. The prevalence and causes of left ventricular dysfunction (LVD) were explored. METHODS: In total, 1869 patients of a pacemaker outpatient clinic were screened for left ventricular systolic dysfunction by transthoracic echocardiography. All patients were interviewed for symptoms and cardiologist care. Percentages of RV pacing and underlying cardiac disease were recorded. RESULTS: A left ventricular ejection fraction (LVEF) under 45% was found in 207 (11.1%) of all patients. Predictive factors for a reduced LVEF were a high pacing rate and long-term pacing. LVD due to RV pacing was diagnosed in 3.4% of all patients. Only 845 patients (45%) reported that they regularly visited a cardiologist. CONCLUSION: There is a high prevalence of unknown LVD in a typical pacemaker cohort. Therefore, regular echocardiographic examinations should be performed in outpatients of pacemaker clinics.